ARCHAEOLOGICAL EXPLORATIONS ABOVE AND BELOW GROUND AT HORVAT MIDRAS, JUDEAN FOOTHILLS, ISRAEL - Boaz ZISSU; Amir GANOR; Rina AVNER; Alon KLEIN (Journal of Ancient History and Archaeology)
Horvat Midras is situated in the central Judean Foothills, approximately 6 km northeast of the Roman city of Beth Guvrin–Eleutheropolis, alongside the primary Roman route to Jerusalem. At its zenith during the Roman period in the 1st century CE, the settlement spanned over 12 hectares, making it one of the largest ancient rural sites in the area. This Jewish settlement was destroyed during the Bar Kokhba Revolt (132–136 CE). Our excavation team uncovered a Late Antique church in the northern section of the village. Beneath the church floor, we found earlier strata that include remains of a building and underground chambers from the Late Hellenistic to Early Roman periods. These interconnected underground chambers, forming a typical hiding complex, fell out of use after the Bar Kokhba Revolt. Following a period of abandonment in the 2nd and 3rd centuries CE, the remnants of the earlier structures were leveled to make way for a new basilica, which featured a white mosaic floor. This construction, dating to the 4th century CE, was linked to a venerated rock-cut tomb, which we believe was the primary purpose of the architectural complex. The tomb, created within a rock-cut chamber integrated into the earlier hiding complex, also dates to the 4th century. In the subsequent architectural phase, a basilical church with marble columns, capitals, and exquisite multicolored mosaic floors was built within the former basilica, reusing some of its columns and walls. The apse was constructed above the tomb, with access provided via a room north of the apse that served as a martyrium. We identified at least two construction phases for this church, distinguished by the mosaics in their floors. The second phase, dating to the third quarter of the 6th century CE, involved extending the bema westward, sealing the passage between the north aisle and the martyrium, creating a new northern entrance to the martyrium, and constructing what appears to be a baptismal font atop the passage leading from the martyrium to the empty tomb. Numismatic evidence and the style of the mosaics and capitals support this dating. The structure remained in use during the Umayyad period until its destruction in the earthquake of 749 CE. As at other sites in the Judean Foothills, the study of the subterranean chambers carved out of the local chalk provides valuable insights into the site’s history. The survey revealed nearly 60 artificial cavities and subterranean complexes, including cisterns, quarries, columbaria, ritual immersion baths, and storerooms. Ten cavities beneath the ancient settlement contained typical hiding complexes, which, along with the artifacts found, offer important information about the settlement during the late Second Temple period and the Bar Kokhba Revolt. Additionally, dozens of rock-cut tombs were excavated from the surrounding slopes. One decorated hypogeum built of ashlars dates to the 1st and 2nd centuries CE. This hypogeum is connected by a tunnel to a smaller rock-cut tomb with three arcosolia, hewn during the Byzantine period. Red crosses and the Greek letters ΙΧ (iota and chi, representing Ιησους Χριστος, or Jesus Christ) and ΑΩ (alpha and omega, alluding to Jesus’s statement “I am the Alpha and the Omega, the first and the last, the beginning and the end” [Revelation 22:13]) were found on the tomb walls.